2020
DOI: 10.1007/s10741-020-09927-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of serum C-reactive protein in heart failure with preserved ejection fraction: a systematic review and meta-analysis

Abstract: Heart failure (HF) is a major epidemic with rising morbidity and mortality rates that encumber global healthcare systems. While some studies have demonstrated the value of CRP in predicting (i) the development of HFpEF and (ii) long-term clinical outcomes in HFpEF patients, others have shown no such correlation. As a result, we conducted the following systematic review and meta-analysis to assess both the diagnostic and prognostic role of CRP in HFpEF. PubMed and Embase were searched for studies that assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
0
33
0
1
Order By: Relevance
“…Risk stratification in HF is an important clinical problem ( 24 , 25 ). Previous studies have elucidated that the demographics of patients with HFmrEF lied in between those of HFpEF and HFrEF patients, but in general were more similar to HFpEF patients, with a heavier burden of hypertension and atrial fibrillation/flutter ( 10 , 12 , 13 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk stratification in HF is an important clinical problem ( 24 , 25 ). Previous studies have elucidated that the demographics of patients with HFmrEF lied in between those of HFpEF and HFrEF patients, but in general were more similar to HFpEF patients, with a heavier burden of hypertension and atrial fibrillation/flutter ( 10 , 12 , 13 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the characteristics and clinical outcomes of HFmrEF patients among subgroups defined by the prior directional changes in LVEF are significantly different. Risk stratification in HF is an important clinical problem (24,25). Previous studies have elucidated that the demographics of patients with HFmrEF lied in between those of HFpEF and HFrEF patients, but in general were more similar to HFpEF patients, with a heavier burden of hypertension and atrial fibrillation/flutter (10,12,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that CRP, a biomarker of systemic inflammation produced in response to interleukin-6 by inflammatory cells, has both diagnostic and prognostic value in predicting the risk of developing HFpEF and subsequent CV events. However, the results of the studies are conflicting [ 134 ].…”
Section: Cmd With Non-obstructive Atherosclerosismentioning
confidence: 99%
“…Inclusion of patients with ischemic symptoms at hospital presentation may create a selection bias. The current study did not test for other biomarkers such as brain natriuretic peptides (BNPs) and High Sensitivity C-Reactive Protein (hsCRP) (39). Overall, we consider this research preliminary and encourage replication.…”
Section: Discussionmentioning
confidence: 95%